Study on tower crane / Nurul Hayati Abdul Halim … [et al.] - Abdul Halim, Nurul Hayati; Yaakob, Mastura; Mansor, Ainun (2003)
A nation that moves towards development, industrialization cannot avoid using machines as part of the devices of operations. In the construction industry, a tower crane is widely used as an important device for operations. The purpose of this project is to study the concepts of tower cranes in terms of their functions requirement, performances, the purpose of design, economics, and many more. We also considered safety measures and improvements in the quality of the machine's operations.